Pengaruh Back Massage Menggunakan Olive Oil terhadap Risiko Dekubitus pada Pasien Stroke di Ruang ICU RSI Sultan Agung - Arum Puspa Suryani Putri; Ahmad Ikhlasul Amal (Lembaga Pengembangan Kinerja Dosen, 2025)
Stroke patients often experience mobility impairments, which increase the risk of developing pressure ulcers (decubitus). Pressure ulcers are a common complication for patients with limited mobility, especially in the ICU. One intervention that can be used to reduce the risk of pressure ulcers is back massage using olive oil. This study aims to analyze the effect of back massage using olive oil on reducing the risk of pressure ulcers in stroke patients in the ICU at Sultan Agung Hospital. This study used a pre-experimental design with a one-group pretest-posttest approach, involving 17 respondents who received back massage using olive oil. The results showed that most respondents were aged 56-65 years (35.3%), the majority were male (70.6%), with comorbidities such as diabetes mellitus (52.9%), and the length of hospitalization was 3-5 days. Before the intervention, most respondents were categorized as being at moderate risk based on the Braden scale; however, after the intervention, the majority were no longer at risk of pressure ulcers. The Wilcoxon test showed a p-value of 0.001, indicating that back massage using olive oil had a significant effect on reducing the risk of pressure ulcers. In conclusion, back massage using olive oil is effective in reducing the risk of pressure ulcers in stroke patients in the ICU. Therefore, this technique can be used as an alternative intervention to prevent the occurrence of pressure ulcers in stroke patients.